Quality of Life in Palliative Care for Patients with Renal Failure: A Bibliometric Analysis - Dian Ratri; Erna Rochmawati (Indonesian Journal of Global Health Research, 2026)
Quality of life is a key outcome in palliative care for patients with chronic kidney disease (CKD), especially in advanced stages and patients undergoing dialysis. Although publications on QoL in palliative care for CKD continue to increase, the global knowledge landscape remains scattered and has not been comprehensively mapped through a bibliometric approach. Objective to map publication performance, the geographical distribution of country contributions, and the dynamics of research themes related to QoL in palliative care for CKD through bibliometric analysis. A bibliometric study was conducted using the Scopus database (Elsevier) with the range 10 years . The search strategy combined the keywords palliative care/support, CKD/ESRD/dialysis, and QoL/health-related QoL. The initial search yielded 1,077 documents, which were then narrowed down to 681 publications (last 10 years), 654 publications (Medicine and Nursing fields), and finally 561 documents (article and review types) for analysis. Descriptive analysis was used for annual publication trends (2016–2026) and country contributions, while keyword co-occurrence mapping, overlay maps, and density maps were performed using VOSviewer version 1.6.18. Publication production showed an increasing trend from 37 documents (2016) to a peak of 69 documents (2025), with 2026 recording 1 document that was likely temporary. Country contributions were dominated by the United States (198 documents), followed by the United Kingdom (92), Australia (74), and Canada (45). The co-occurrence map places the terms population and service context as central nodes (human/humans, male, aged, article) and shows major clusters reflecting (1) CKD themes and management related to dialysis/hemodialysis as well as palliative and conservative care, (2) comorbidities, symptoms, and clinical indicators related to disease burden (e.g., fatigue, pruritus, anemia, hypertension, sepsis, depression, creatinine, acute kidney failure), and (3) hospital service context and study design (hospitalization, observational/retrospective study). The overlay map indicates a strengthening of the themes of service outcomes and follow-up (follow-up, clinical outcome, hospitalization) as well as an increased focus on patient-centered approaches and psychosocial support (patient-centered care, nurse, interpersonal communication, qualitative research). The density map confirms the largest hotspots in the terms of population (male, aged) and kidney service/therapy themes (palliative care, dialysis/hemodialysis, CKD) that are interconnected with comorbidities and service outcomes. QoL research in CKD palliative care is growing consistently and is dominated by countries with established research ecosystems, with the main themes still strongly centered on the clinical and service context (dialysis/hemodialysis, CKD, comorbidities, inpatient outcomes). However, there are indications of a strengthening research direction towards patient-centered approaches, communication, caregivers, and qualitative methods. Future studies need to strengthen the measurement of QoL outcomes that are meaningful to patients and families, expand the geographical context, and evaluate palliative-nephrology integration models that can tangibly improve QoL.